Factors influencing consumer’s impulse purchase behaviour among Faculty of Business and Management students in UiTM Cawangan Melaka Kampus Bandaraya Melaka / Nazwa Nurshahida Mohamed Nazaruddin - Mohamed Nazaruddin, Nazwa Nurshahida (Faculty of Business and Management, 2019)
The impulse purchase behaviour among the consumer could be great opportunities for every seller or retailers to increase their sales and directly the profits as well which makes this kind of behaviour are pretty much welcomed in every store. However, it has been related to the increase of debt, wasting money, illiteracy on personal financing and lack of sense on differentiate needs and wants of a consumer. Hence, the aim of this study is to examine the factors influencing consumer’s impulse purchase behaviour among Faculty Business and Management students in UiTM Cawangan Melaka Kampus Bandaraya Melaka. The dependent variable in this study was consumer’s impulse purchase behaviour while the independent variables were made up of four variables which are prominent product display, broad assortment, price promotion and customer characteristic. A total of 308 respondents has completed the survey questionnaire and the Statistical Package for Social Sciences Software (SPSS) was used to analyse all the data obtained. A multiple regression analysis was used to test the relationship among the variables. The result indicates that broad assortment, price promotion and customer characteristic have significant relationship with impulse purchase behaviour. The most significant predictor variable of consumer’s impulse purchase behaviour is customer characteristic which found that customer characteristic that are tend to impulse purchases will be have more tendency to be influenced for impulse purchase behaviour. The findings of this research can be very helpful and useful to producers, retailers, companies and marketers as well to improve and increase the potential of more profits and presenting a better image or perception towards the consumers. This research could be helping the consumer on understanding and realizing the tricks that were done by companies or marketers to make them pay and spend more.